Plumbism (Chronic lead poisoning): A Health Hazard at Ship Breaking Industry (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Plumbism which is commonly known as chronic lead poisoning may occur due to prolong use of vermilion, dye and cosmetics containing lead.Objectives: To determine plumbism by observing the clinical features and problems among the workers of ship breaking industry and to draw attention of the legal authorities to take necessary measures and steps for prevention. Methods: A cross sectional study was conducted at ship breaking industry, Shitakunda, Chittagong in the month of February 2012 among 100 ship breaking workers. Data was collected by direct observation and face to face interview by semi structured questionnaire.Results: A total 100 respondents, 83% (n=83) were found various features of plumbism, 81.93% (n=68) were male and 18.07% (n=15) were female. Maximum workers developed features of plumbism were after exposure to ship breaking industry within 6 to 9 months and the incidence was 27.72% (n=23). Different types clinical features like facial pallor, anaemia, blue line lead (Burtonian line) in the gum, colicky abdominal pain, constipation, hypertension, paresthesia, menstrual disorders, sterility, history of abortion and various general symptoms stand for 66.26% (n=55), 60.24% (n=50), 48.19% (n=40), 89.15% (n=74), 77.1% (n=64), 30.12% (n=25), 8.43% (n=7), 14.45% (n=12), 9.63% (n=8), 3.61% (n=3), 45.78% (n=38) respectively.Conclusion: Lack of knowledge and cautiousness most of the workers suffer from various types of medical problems. Plumbism is one of those. Precautionary steps should be taken to prevent lead toxicity among workers in the ship breaking industries are must, such as using personal protecting equipments (mask, moisting device etc.), to establish and follow workers friendly company rules, strict monitoring of onsite lead concentration, maintenances of proper ventilation,periodical heath check up and further exposure should be avoided if clinical features of lead poisoning once appear etc.J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 38-41